A guerra fluvial: a expansao neerlandesa, a construcao de fortificacoes e a engenharia indigena no Maranhao e Grao-Para (1621-1641) - SOUSA, Karolynne Soares (2019)
In the Seventeenth century, the River War was the representation of how the Dutch expansion in the region of the former Maranhão and Grão-Pará states, thematic to be analyzed in the present study, from the constructions of fortifications and how these were constituted by the cooperation and indigenous engineering, main actors of this narrative. It will be demonstrated, initially, how the Dutch Atlantic was constituted with the consolidation of the Iberian Union and fragmentation of commercial relations between Hispanics and the Low Countries, and consequently, the rebellion against Hispanic monarchy. Therefore, it will be studied how the experiences of wars that occurred in the State of Maranhão and Grão-Pará, different from those promoted in the State of Brazil, were fundamental for the establishment of the Dutch Amazon in the Sixties and how the indigenous collaboration fomented trade and piracy through the Tupinamba routes. It will be shown at the end of the study how the Dutch established and maintained their power relations in the Amazon Delta, taking as a scenario the fortifications built by the indigenous, essential coats. It was used the scientific methodology, having as a deductive approach, having as base theoretical reference the Overseas Archive, General Archive of Simancas, Archivo General de Indias, Nationaal Archief (The Hague) and sources of the National Library of Rio de Janeiro, as well as the letters, applications, and crafts that were written between the Iberian kingdoms and the officers or travelers who were in the region in the period of the seventeenth century, characterizing the historical method.